Habitat use and foraging parameters of breeding Skylarks indicate no seasonal decrease in food availability in heterogeneous farmland. Issue 1 (26th January 2022) - Püttmanns, Manuel; Böttges, Laura; Filla, Tim; Lehmann, Franziska; Martens, Annika Sophie; Siegel, Friederike; Sippel, Anna; von Bassi, Marlene; Balkenhol, Niko; Waltert, Matthias; Gottschalk, Eckhard
Abstract: Reduced food availability during chick raising is a major driver of farmland bird declines. For the Eurasian Skylark ( Alauda arvensis ), food availability is determined by various factors (i.e., arthropod abundance/diversity, accessibility of the vegetation, distance to foraging sites). In modern farmland, it is supposed to decrease over the breeding season due to less penetrable vegetation. We explored foraging habitat selection by chick‐raising Skylarks with a focus on the seasonal dynamics of habitat use and food availability. We investigated (i) habitat selection concerning prey biomass/diversity, vegetation cover, and distance to foraging sites, (ii) the overall and seasonal habitat use, and (iii) seasonal developments of foraging parameters (e.g., the feeding frequency) as indicators of food availability. We collected data on foraging habitats and foraging parameters of chick‐raising Skylark pairs at 51 nests from a Central European population in 2018 and 2019. Prey biomass/diversity and vegetation cover were measured for all habitats around 42 of these nests. As revealed by multivariate and compositional analyses, Skylarks mainly selected foraging habitats based on the proximity to nests. The most frequent habitats within home ranges could not be ranked according to an overall importance for foraging and their use partially changed over time. The feeding frequency increased throughout the breeding season, while other foraging parameters did not show significant changes. In contrast to our expectations, our data indicated therefore an increase, not a decrease in food availability in the late breeding season. This also implies that the way in which Skylarks used habitats was constantly suitable to raise offspring. We interpret this to be a consequence of the heterogeneous farmland composition of the study area that enabled Skylarks to establish a diverse home range and to benefit from the synergetic effects of neighboring habitat types. Thus, our findings provide support for the high importance of crop diversity in Skylark conservation. Abstract : The Eurasian Skylark ( Alauda arvensis ) is thought to suffer from a decrease in food availability .in European farmland during the breeding season. In contrast to this, our multivariate analyses of habitat selection and foraging parameters of chick‐raising pairs in Central Europe suggest no seasonal food shortage. We interpret our findings as being a consequence of the heterogeneous composition of our study area and highlight the importance of crop diversity in Skylark conservation.